Counselling services in prevention of mother-to-child transmission (PMTCT) in Delhi, India: An assessment through a modified version of UNICEF-PPTCT tool. Issue 1 (March 2015) - Kumar, Arvind; Singh, Bir; Kusuma, Yadlapalli S.
Abstract The study aims to assess the counselling services provided to prevent mother to child transmission of HIV (PMTCT) under the Indian programme of prevention of parent-to-child transmission of HIV (PPTCT). Five hospitals in Delhi providing PMTCT services were randomly selected. A total of 201 post-test counselled women were interviewed using a modified version of the UNICEF-PPTCT evaluation tool. Knowledge about HIV transmission from mother-to-child was low. Post-test counselling mainly helped in increasing the knowledge of HIV transmission; yet 20%–30% of the clients missed this opportunity. Discussion on window period, other sexually transmitted diseases and danger signs of pregnancy were grossly neglected. The PMTCT services during the antenatal period are feasible and agreeable to be provided; however, certain aspects, like lack of privacy, confidentiality of HIV status of the client, counsellor's 'hurried' attitude, communication skills and discriminant behaviour towards HIV-positive clients, and disinterest of clients in the counselling, remain as gaps. These issues may be addressed through refresher training to counsellors with an emphasis on social and behaviour change communication strategies. Addressing attitudinal aspects of the counsellors towards HIV positives is crucial to improve the quality of the services to prevent mother-to-child transmission of HIV.